Cytotoxicity of Lentinus isolates mycelial extracts on human colorectal carcinoma HCT-116 cells - Rich Milton R. Dulay, Esperanza C. Cabrera, Sofronio P. Kalaw, Renato G. Reyes, Jerwin R. Undan (Journal of Applied Pharmaceutical Science, 2022)
Medicinal mushrooms are considered as potent natural sources for drug discovery and are of great interest in anticancer research worldwide. The cytotoxicity of rich macrofungal diversity in the Philippines remains to be largely unexplored. One of the macrofungal groups is Lentinus. Lentinus species (Polyporaceae, Basidiomycota) are woodrotting mushrooms that naturally growing solitary or more often in groups on water-soaked logs, woods, and trunks of trees. They are important resources of functional food and bioactive metabolites. The present work evaluated the cytotoxicity of the ethanolic extracts of mycelia of the 15 Lentinus isolates against two cancer cell lines, human colorectal carcinoma (HCT-116) and hepatocellular carcinoma (HepG2), and one normal cell line, HK-2 normal kidney epithelial using the MTS proliferation assay. All Lentinus mycelial extracts showed concentration-dependent cytotoxicity against HCT-116. The IC50 values of mushroom extracts ranged from 242.75 to 444.79 µg ml−1 for HCT116 colon cancer cells. Among the mushroom extracts, Lentinus strigosus CL-01 extract was the most potent with the lowest IC50 value, whereas Lentinus sajor-caju LSCBot extract registered the highest IC50 value. On the other hand, extracts were not cytotoxic to HepG2 and HK-2 cell lines with less than 50% cytotoxicity indices. Therefore, the mycelia of 15 Lentinus isolates tested can be considered as potential sources of cytotoxic compounds for colon cancer. However, furtherance of the cytotoxicity and other bioactivity profiling of Lentinus mycelial extracts is highly recommeded.
Keywords: L. strigosus CL-01, Philippine Lentinus, mycelial biomass, anti-cancer